Analisis Implementasi Inventarisasi Aset Berdasarkan PP Nomor 28 Tahun 2020 dalam Meningkatkan Pengelolaan Aset Daerah (Pada Pemerintah Kota Cimahi) - Siti Nur Anisya; Jouzar Farouq Ishak; Arwan Gunawan (Indonesian Accounting Research Journal, 2021)
Cimahi City Government has certified assets less than 50% with a total of 516 assets. This research aims to find out more about asset’s administration of Cimahi City according to PP number 28 of 2020. The method used in this research is qualitative method, by using interview data collection technique, observation, and literature study. The result of this research proves that regional asset’s administration in Cimahi has used PP number 28 of 2020, but the socialization process is still not prevalent. There are obstacles faced by Cimahi City Government in regional asset’s administration for improving regional asset management is arduous to acquire data from each regional work unit. This research is expected to be capable of assisting in explaining how regional asset’s administration process in accordance to PP number 28 of 2020, and giving advantages for many parties.